Iniciação científica na graduação de medicina da universidade federal do pará: a percepção do acadêmico - CARVALHO, Deyvid Brian Cavalcante Carlos de (2023)
Medical education is an important issue throughout the world, raising even more interest in the era of globalization. In Brazil, the discussions around medical education increased dramatically during the construction of the Unified Health System and got even more intensive after the establishment of the National Curricular Guidelines. However, very little is known about possible relations and mutual influences between medical education and scientific research. In the 2007 edition of the National Examination of Student Performance — ENADE 2007, 30.7% of the students from medical schools had not participated in Scientific Initiation activities (a program of research activities for undergraduate students) during their courses, 31% had no opinion, 39% of them had participated in such activities and 12% had done so informally. For 10.9% of the students there were no Scientific Initiation activities available and 6.5% reported the existence of such activities however on an extra curricular basis. It is noteworthy that in 2003 only 20.9% of the students reported that joining these research activities was important for their medical education while 30.7% of them reported not participating in research activities In the present study we investigated the availability of Scientific Initiation activities in the course of sixth year medical students from Universidade Federal do Pará in Brazil. Special attention was paid to the reasons for enrolling or not in the program. Even with an increased participation of students in the program we identified a great number of reasons why students did not participate although 90% of them consider that participation in the program should be mandatory for medical students in general.